ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT.MODERNLAND REALITY Tbk - Ningsih, Retno Wahyu (EKONOMIA, 2019)
The purpose of this study was to determine the financial performance of the periode 2010 - 2012 before the acquisition and in the periode 2014 - 2016 after the acquisition at PT. Modernland Realty Tbk.The liquidity ratio (current ratio ) produced by PT Modernland Reality Tbk,after the 2014 - 2016 periode was greater than in the periode 2010 - 2012 before acquisition because all current assets compenents of PT. Modernland Reality Tbk in the 2014 - 2016 periode were more maximal in convering its shorts - term debt obligations or company management has been maximized in managing their finances to fulfiil all financial obligations for the periode of 2014 - 2016.The solvency ratio ( total debt to assets ) generated by PT.Modernland Reality Tbk,after the acquisition in the periode 2014 -2016 was greater than the periode of 2010 - 2012 before acquisition due to the total assets owned by PT.Modernland Reality Tbk in the periode of 2014 - 2016 is more maximally used in fulfilling all of its long – terliabilities or total debt if compared to 2010 - 2012.The profitability ratio ( return on investment ) produced by PT.Modernland Reality Tbk after the acquisition in the 2014 - 2016 periode was greater than in the 2010 - 2012 before the acquisition,because of the increase in profitability due to an increase in sales and an increase in the net profit of EAT PT.Modernland Reality business,so that the profits obtained are more maximal.